Native woody vegetation in central Argentina: Classification of Chaco and Espinal forests - Cabido, Marcelo; Zeballos, Sebastián R.; Zak, Marcelo; Carranza, María L.; Giorgis, Melisa A.; Cantero, Juan J.; Acosta, Alicia T. R. (Applied vegetation science, 2018)
Question: What are the composition and spatial patterns of native woody plant communities in the southern Great Chaco and Espinal? Location: Córdoba Province, central Argentina, an area of ca. 161,000 km2. Methods: We collected 351 geo-referenced relevés representative of the geographic, topographic and ecological variation of the Chaco and Espinal woody vegetation in central Argentina. The relevés were classified into vegetation types using the hierarchical ISOPAM method. Forest and shrubland types were described on the basis of diagnostic species occurrences and their distribution in relation to environmental factors. A map of the actual vegetation derived from remote-sensed images (Landsat) and field data was used to describe the current distribution and abundance of the different vegetation types. Results: The classification of the 351 plots × 837 species matrix revealed two major clusters comprising seven woody vegetation types corresponding to Chaco lowland and mountain forests and shrublands, Espinal forests and edaphic vegetation. The most important gradients in woody vegetation types are related to elevation, temperature and rainfall variables. Conclusions: Subtropical seasonally dry woody plant communities from the southern extreme of the Great Chaco and Espinal forests were described for the first time based on complete floristic data. Our results show that lowland Chaco native forests, as well as replacement communities, are still present in its southern distribution range and are well distinguishable from other vegetation types such as the Espinal and mountain forests. Overall, extensive Espinal forests have almost disappeared while Chaco vegetation is highly fragmented and degraded.